A Pedagogical Model in a Non-Formal Educational Context: The Museum - Alfageme González, Mª Begoña; Martínez Valcárcel, Nicolás (Education Policy Analysis Archives, 2007)
Our proposal is to present a model of educational planning for museums. The school cannot be assumed to render all the education that a person needs. Therefore other social institutions are called upon to complement a person?s training. We begin by justifying the interest of including non-formal education in this context. Subsequently, we focus our study on an educational model that can be used as a planning tool in museums, thus expanding its use as a formative institution as well.